Polimorfisme P2Y12 Terhadap Agregasi Platelet Pada Pasien Penyakit Jantung Koroner - oktaviarika dewi hermawatiningsih (Parapemikir : Jurnal Ilmiah Farmasi, 2019)
Genetic polymorphism of P2Y12 receptor is one of the factors responsible for the variation in response to antiplatelet therapy. Variations in response to P2Y12 receptors can cause Coronary Artheri Disease (CAD) in CHD patients. This research was conducted in RSUD Sidoarjo East Java  from  November  to December 2017 which aims to determine the effect of P2Y12 polymorphism on platelet aggregation in CHD patients. The research method used is Polymerase Chain Reaction (PCR) for P2Y12 genetic polymorphism and Light Transmittance Aggregometry (LTA) method for platelet aggregation measurement. From 30 samples, it was found that all samples had homozygot (wild type) type P2Y12 polymorphism with bp value of about 156 bp. Inferential analysis  was conducted  to determine the relationship between polymorphism of P2Y12 with platelet aggregation obtained p value = 0,130. From these results it can be said  that  between the genetic polymorphism of P2Y12 and platelet aggregation has no significant relationship.  Keywords : antiplatelet; clopidogrel; platelet aggregation; polymorphism P2Y12.